Synovial metaplasia in lipoma - Michal, M; Zámecník, M (The American Journal of dermatopathology, 1998)
We present a unique case of a lipoma with widespread synovial metaplasia. A 52-year-old woman had a recurrence 1 year after excision of a subcutaneous lipoma of the neck. Histologically, the primary tumor was an ordinary lipoma. The recurrent tumor was a myxoid lipoma with synovial metaplasia. The synovial metaplastic process manifested as labyrinthlike clefts, which were lined by one or more synovial-like cell layers. Ultrastructurally, the synovial metaplastic cell had secretory, phagocytic, and fibroblastlike features.
Keywords: Skin Neoplasms; Metaplasia; lokální recidiva nádoru; lipom; metaplazie; Synovial Membrane; lidé; Lipoma; Neoplasm Recurrence, Local; Skin; nádory kůže; ženské pohlaví; lidé středního věku; synoviální membrána; Humans; Middle Aged; Female; kůže